ESP Requirements in Vocational Education: Insights from Computer and Network Engineering Department - Helingo, Adimawati; Molou, Fadli Setiawan (Al-Lisan: Jurnal Bahasa, 2022)
This study aims to determine the learning situation and needs of English language specific to the field of computer and network engineering department in vocational schools seen from the perceptions of students, English teachers, and the head of the department. This survey research was conducted in 21 state vocational high schools spread across Gorontalo province involving 211 computer and network engineering students, 21 English teachers, and 21 department heads as respondents. The questionnaire instrument was distributed to students to find out the English language and methods they need according to their major, while interviews were conducted with English teachers and the head of the department to explore information related to the implementation of English language learning at school and what kind of English language methods and materials are needed by students so that they can be useful in the world of work as the students graduate. The questions asked covered the aspects of necessity, lack, and wants. The results show that English learning in vocational schools is still dominantly using general English even though English teachers are well aware of the importance of specific English for the students. The teachers and head departments of computer and network engineering agree to the collaborative teaching method involving both English and the subject-specific teacher to provide a more relevant and specific learning environment in vocational settings.